2018
DOI: 10.3390/jcs2010013
|View full text |Cite
|
Sign up to set email alerts
|

Milling of Nanoparticles Reinforced Al-Based Metal Matrix Composites

Abstract: This study investigated the face milling of nanoparticles reinforced Al-based metal matrix composites (nano-MMCs) using a single insert milling tool. The effects of feed and speed on machined surfaces in terms of surface roughness, surface profile, surface appearance, chip surface, chip ratio, machining forces, and force signals were analyzed. It was found that surface roughness of machined surfaces increased with the increase of feed up to the speed of 60 mm/min. However, at the higher speed (100-140 mm/min),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…However, no explanation related to thermal softening or strain hardening effects was given as compared to [59] (Figure 25Figure 25). However, Xiong et al [61] have claimed that feed rate had the most dominant effects on cutting force when micro-milling Al/TiB 2 instead of filler content or cutting speed due to their influences on increasing shear angle and decreasing friction angle while Pramanik et al [62] confirmed that the increase of material removal rate (MRR) at high feed rates contributed to cutting force escalation.…”
Section: Micromachining Of Nano-ceramic Based Nanocompositesmentioning
confidence: 99%
“…However, no explanation related to thermal softening or strain hardening effects was given as compared to [59] (Figure 25Figure 25). However, Xiong et al [61] have claimed that feed rate had the most dominant effects on cutting force when micro-milling Al/TiB 2 instead of filler content or cutting speed due to their influences on increasing shear angle and decreasing friction angle while Pramanik et al [62] confirmed that the increase of material removal rate (MRR) at high feed rates contributed to cutting force escalation.…”
Section: Micromachining Of Nano-ceramic Based Nanocompositesmentioning
confidence: 99%
“…And the optimum technological parameters are selected. Alokesh Pramanik et al [9] performed milling on nanoparticle reinforced aluminum matrix composites. The results show that the surface roughness of the workpiece increases with the increase of feeding speed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there is an increasing demand for using the nanoparticle reinforced metal matrix nanocomposites (MMCs) in the aircraft and biomedical sectors [ 1 ]. This is due to their excellent properties such as high corrosion resistance, high specific strength, and high elastic modulus over pure metals [ 1 , 2 , 3 ]. In general, MMCs have lightweight metals such as titanium, titanium alloy, aluminum, and the reinforcements are nanomaterials in the form of particle/fiber having higher-strength.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the machining forces for TiB 2 /Al MMCs were slightly higher and the surface roughness was lower than that for the non-reinforced alloy with increasing cutting speed mainly due to the material flow. Pramanik et al [ 3 ] studied the machinability of SiC/Al nanocomposite with 10% volume fraction of SiC particles by face milling and investigated the effect of cutting speed and feed rate on surface roughness, machining forces, and chip surface. They found that chip ratio, surface roughness, and machining forces were affected by feed rate and cutting speed.…”
Section: Introductionmentioning
confidence: 99%